PHYSICAL DEVELOPMENT OF CHILDREN AND ADOLESCENTS IN THE REPUBLIC OF UZBEKISTAN: ISSUES OF STUDY AND ASSESSMENT (Modern education and development, 2025)
The article presents an analysis of studies on the physical health (physical development and physical fitness) of children, adolescents, and young people living in Uzbekistan. It examines the influence of environmental and socio-economic factors on physical health indicators. Special attention is given to the role of the ethnic factor in shaping the physical health of this population category.